Overnight storage of whole blood: cooling and transporting blood at room temperature under extreme temperature conditions. Issue 2 (12th September 2013) - Thibault, L.; Beauséjour, A.; Jacques, A.; Ducas, É.; Tremblay, M.
<x xml:space="preserve">Abstract</x> Background and Objectives Many countries allow the overnight storage of whole blood (WB) at ambient temperature. Some countries, such as Canada, also require a rapid cooling of WB with an active cooling system. Given the significant operational constraints associated with current cooling systems, an alternative method for cooling and transporting WB at 20–24°C was evaluated. Materials and Methods Phase 22 cooling packs (TCP Reliable Inc., USA) were used in combination with vacuum‐insulated panel (VIP) boxes. Temperature profiles of simulated WB units were studied in extreme temperatures (−35 and 40°C). The quality of blood components prepared using Phase 22 packs and CompoCool‐WB (Fresenius HemoCare, Germany) was studied. Results Phase 22 packs reduced the temperature of simulated WB bags from 37 to 24°C in 1·7 ± 0·2 h. Used in combination with VIP boxes, Phase 22 packs maintain the temperature of bags between 20 and 24°C for 15 and 24 h, compared to 2 and 11 h with CompoCool‐WB, when exposed at −35 and 40°C, respectively. The quality of platelet concentrates and plasma was comparable, regardless of the cooling system used. For red blood cell units, per cent haemolysis on day 42 was slightly higher in products prepared after cooling with Phase 22 packs compared to CompoCool‐WB (0·33 ± 0·15% vs. 0·21 ± 0·06%; P < 0·05). Conclusions Phase 22 packs combined with VIP boxes are an acceptable alternative to butane‐1, 4‐diol cooling systems. This system allows blood manufacturers to transport WB to processing facilities in a broad range of environmental conditions.